2005
DOI: 10.1139/s04-059
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale struvite recovery from anaerobic digester supernatant at an enhanced biological phosphorus removal wastewater treatment plant

Abstract: Pilot testing of a fluidized bed reactor used to recover phosphate, in the form of struvite, from anaerobic digester supernatant was conducted at the Advanced Wastewater Treatment Plant, City of Penticton, British Columbia. The main objective of this study was to demonstrate the ability of the reactor to remove at least 70% of the phosphate in the supernatant from a digester fed with a combination of primary and secondary sludge. It was found that the operation of the reactor could be controlled to achieve any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 17 publications
3
61
0
8
Order By: Relevance
“…concentration is 2 -3% (Liao et al, 2005) which allows for more efficient struvite recovery (Britton et al, 2005;Pastor et al, 2008;Shen, 2010). The enhanced PO 4 3-concentrations in sewage sludge and the ease with which it is released from the microbial biomass increases the risk of struvite scale formation in the pipelines.…”
Section: Enhanced Biological Phosphorus Removal (Ebpr)mentioning
confidence: 99%
See 1 more Smart Citation
“…concentration is 2 -3% (Liao et al, 2005) which allows for more efficient struvite recovery (Britton et al, 2005;Pastor et al, 2008;Shen, 2010). The enhanced PO 4 3-concentrations in sewage sludge and the ease with which it is released from the microbial biomass increases the risk of struvite scale formation in the pipelines.…”
Section: Enhanced Biological Phosphorus Removal (Ebpr)mentioning
confidence: 99%
“…It has been reported that 58-94% P recovery is possible through formation of struvite from EBPR in wastewater treatment plants Britton et al, 2005;Marti et al, 2008). However, the recovery efficiency varies depending upon sludge characteristics (Pastor et al, 2008).…”
Section: Enhanced Biological Phosphorus Removal (Ebpr)mentioning
confidence: 99%
“…Of the 3.4 × 10 10 gallons of drinking water produced annually by public water systems in the US, approximately 63% is used for residential purposes (indoor and outdoor) [43]. Of that, 42% of annual residential use was for indoor purposes and 58% for outdoor purposes (without taking into account firefighting allocation) based on the evaluation of 1188 homes from 14 cities across six regions of the US.…”
Section: Water Demand and Water Usementioning
confidence: 99%
“…The wastewater is treated as waste to be eliminated with the investment of large amount of energy and materials, regardless of the potential value of wastewater constituents. For instance, even though phosphorus fertilizer production from easily accessible phosphate rock could be depleted in 50-100 years and cause global food security issues [7,8], expensive treatment technologies are used to remove phosphorus as waste from wastewater to reduce eutrophication in receiving water [9][10][11][12][13]. Emerging chemical and biological contaminants from wastewater and eroded sediments penetrate into the source water, making the treatment of drinking water more technically and financially challenging [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus based-fertilizer recovery, in the form of 99.9% pure struvite also known as magnesium ammonium phosphate (MgNH 4 PO 4 •6H 2 O), has been demonstrated successfully in full-scale sidestream treatment using dewatering liquor from anaerobically digested solids (centrate) processed through upflow fluidized bed reactor technologies (Britton et al 2005). Prior research determined the influence of pH, magnesium to phosphorus (Mg:P) molar ratio, and age of urine on purity, pharmaceutical content and pathogen inclusion in struvite precipitated from source-separated urine.…”
Section: Introductionmentioning
confidence: 99%